Efektifitas Website Sebagai Media Promosi Produk Kuliner; Model EPIC Dalam Membangun Awareness Restoran Di Jakarta - Widi Winarso; Dhian Tyas Untari; Fata Nidaul Khasanah (Jurnal Kajian Ilmiah, 2024)
The increasing use of the internet has made it easier to access information that can be used as a medium for conveying something more easily and efficiently. Thus, the study aims to see the Effectiveness of Websites as a Media for Promoting Culinary Products in an effort to build awareness and interest in culinary tourism. The study uses a quantitative method. Where the quantitative research method is a method used to conduct research on a population or sample, which collects data and analyzes data to test a particular hypothesis. The sampling technique in this study is to use Random Sampling or random samples. The number of samples in this study was 100 respondents who already knew the website www.indonesia.travel. The EPIC Model in this study is a method that will measure the dimensions of Empathy (Empathy) from respondents, Persuasion (Persuasion) that can be felt by respondents, Impact (Impact) that can occur in respondents and the approach of the Communication dimension (Communication) that is conveyed to respondents. Based on the results of the study, the final result of the EPIC Rate value is 3.55. This shows that the value is included in the assessment scale with a very effective category. This shows that the website www.indonesia.travel is very effective in conveying information to the public because the promotion is interesting and easy to understand so that it can build awareness and interest in culinary tourism.